Demographic trend in dengue infection - Raja Rajeswari; Radhika Raman; N P Nivek; R Syed Rasheed; R D Niranjhana Raajasri (Journal of Vector Borne Diseases)
Background & objectives: Dengue fever is one of the most common causes of undifferentiated tropical fevers in hospitalized children across India with the highest recorded morbidity and mortality in children less than 15 years of age. Although common, there is still a knowledge gap regarding its epidemiological factors. The aim of this work was to study the clinical profile and demographic trend over the past 5 years in children with confirmed dengue infection. Methods: This was an observational study of children admitted as in-patients over the past 5 years and diagnosed with dengue infection by serology. Categorical data were presented as percentages. Data regarding rainfall was collected from rainfall statistics from the Indian Meteorological department and correlated based on the T-test. The incidence of dengue infection in COVID-19 predominant years was analyzed using the correlation plot and trend of severe dengue infection over the years was noted by a line plot. Results: The study showed a positive correlation between rainfall and an increase in the incidence of cases. There were relatively reduced number of cases during COVID-19 which was interpreted from the correlation plot. The line plot determined the trend of severity of presentation and more severe cases presented in the years 2019, 2021 and 2022. Interpretation & conclusion: Other than the pathophysiology, studies to understand the change in the severity of clinical presentation every year could help in augmenting vector control measures